Patterns of exposure of Iberian wolves (Canis lupus) to canine viruses in human-dominated landscapes - Millán, Javier; López-Bao, José V.; Oleaga, Álvaro; Rodríguez, Alejandro; Esperón, Fernando (2015)
Resumen del trabajo presentado a la II Conferencia Bienal de la Sección Latinoamericana de la Wildlife Disease Association (WDA): "Salud y Enfermedades de la Vida Silvestre en Latinoamerica", celebrada en Bogotá (Colombia) del 24 al 27 de septiembre de 2015.-- et al. Wildlife inhabiting human-dominated landscapes is at risk of pathogen spill-over from domestic species. With the aim of gaining knowledge in the dynamics of viral infections in Iberian wolves (Canis lupus) living in anthropized environments of northern Spain, we analysed samples of 54 wolves by serology and PCR for exposure to four pathogenic canine viruses: Canine Distemper Virus (CDV), Canine Parvovirus-2 (chiefly CPV-2c), Canine Adenovirus 1 and 2 (CAV-1 and CAV-2), and Canine Herpesvirus (CPH). Overall, 76% of the studied wolves presented evidence of exposure to CPV (96% by HI, 66% by PCR), and 75% to CAV (75% by SN, 76% by PCR, of which 70% CAV-1, 6% CAV-2). CPV/CAV-1 co-infection occurred in 51% of the wolves. The probability of wolf exposure to CPV was positively and significantly correlated with farm density, indicating that dog to wolf transmission takes place after wolves are exposed to faeces of guarding or pet dogs during scent communication, or during intra-guild predation events. Exposure to CAV-1 was significantly lower in pups and also lower in autumn, coinciding with the time when pups lose maternally derived immunity (6 out of 7 pups were negative in autumn). CPV and CAV-1 appear to be enzootic in the Iberian wolf population. However, while CPV may depend on periodical introductions by dogs, CAV-1 may be maintained within the wolf population. All wolves were negative for exposure to CDV (by SN and PCR) and CHV (by PCR). The absence of acquired immunity against CDV in this population may predispose it to an elevated rate of mortality in the event of a distemper spill-over via dogs. Peer Reviewed